Learning through the taste system - Scott, Thomas R. (Frontiers in Systems Neuroscience, 2011)
Taste is the final arbiter of which chemicals from the environment will be admitted to the body. The action of swallowing a substance leads to a physiological consequence of which the taste system should be informed. Accordingly, taste neurons in the central nervous system are closely allied with those that receive input from the viscera so as to monitor the impact of a recently ingested substance. There is behavioral, anatomical, electrophysiological, gene expression, and neurochemical evidence that the consequences of ingestion influence subsequent food selection through development of either a conditioned taste aversion (if illness ensues) or a conditioned taste preference (if satiety). This ongoing communication between taste and the viscera permits the animal to tailor its taste system to its individual needs over a lifetime.